Efektivitas Proses Aerasi dan Penggunaan Adsorben Cangkang Telur Bebek & Kepiting dalam Penurunan Fe, Mn, TDS, TOC Pada Air Tanah - Himmatul Aliyah Rosydi; Munawar Ali; Muhammad Abdus Salam Jawwad (Faculty of Engineering, Universitas Serambi Mekkah, 2024)
The parameters of Fe, Mn, TDS and TOC contained in the groundwater around the coast of Gresik Regency can cause unpleasant odours when exposed to air, yellow stains on clothes and health problems for people who consume groundwater. The process of aeration and adsorption treatment can be an alternative to reduce the level of pollutants in groundwater by using crab shells and duck egg shells as adsorbents. The study was conducted by comparing 2 treatment processes, the aeration treatment process using variations in aeration time of 15 minutes, 30 minutes and 45 minutes and the adsorption treatment process using variations in the type of duck and crab eggshell adsorbents. The adsorption process also uses variations in sampling time of 20 minutes, 40 minutes and 60 minutes. In the aeration process, the maximum aeration time for removal of Fe, Mn, TDS and TOC occurs at an aeration time of 45 minutes. The percentage allowance for Fe was 91.4%. The percentage allowance for Mn was 28.6%. The percentage of TDS release was 68.2%. The percentage of TOC addition is 20.8%. In the adsorption process, the maximum samplingtime is 40 minutes. The percentage of Fe removal using duck and crab eggshell adsorbents was 97.8% and 99.2%, Mn was 75.7% and 82.7%, TDS was 84.5% and 94.1%, TOC was 74.6% and 81%. The percentage of adsorbent increases as the stirring time increases, allowing the adsorption process to run properly and optimally.